An Ultra-Wideband (UWB) Ad Hoc Sensor Network for Real-time Indoor Localization of Emergency Responders - Lo, Anthony; Yarovoy, Alexander; Bauge, Timothy; Russell, Mark; Harmer, Dave; Kull, Birgit (IntechOpen, 2011)
None